Implementasi Artificial Intelligence Dalam Game Edukasi Untuk Mengenalkan Tokoh Pahlawan Nasional Dan Meningkatkan Pengetahuan Sejarah - Dikananda, Fatihanursari; Rinaldi Dikananda, Arif; Ash Shiddiqi, Jimly (CV. Multi Kreasi Media, 2024)
History education is an important aspect in education because this field is something that happened in the past and shaped the state of the world so that it can be like today. There are many ways to do history education, ranging from learning through conventional methods, namely by conducting history education learning in the classroom to through methods that are quite popular with elementary school students. the purpose of this paper is to design a history-based educational game that has been made in the storyline used in previous studies and how the results of the study. The stages in this research are the ADDIE model, namely Analysis, Design, Development, Implementation, and Evaluation. The results of this research are educational games on the history of national figures as a means of easy and interesting games and learning for children and based on the results of hypothesis testing after calculating using spss obtained t-count of 27.528, and t-table of 2.0484 where Ha is accepted and H0 is rejected.